PENDIDIKAN KARAKTER ANAK SEKOLAH DASAR DI ERA DIGITAL - Sholikhah; Dini Rakhmawati; Arri Handayani (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Character education has suddenly become a hot topic of discussion in the world of Indonesian education, even though the idea of ​​character is an old idea as old as the history of education, the emergence of the idea of ​​"character education" (character building) has disrupted our nation, especially what is currently sweeping the Indonesian nation. The problems that occur such as violence, corruption, manipulation, lying practices in the world of education ranging from cheating in exams to plagiarism, lack of role models among national leaders, and so on, actually involve issues of character. Even though it is too late to implement character education in schools, "But late than never", there are still many of our generation of students who are in school and need character education so that in the future they will become people who are not only intellectually intelligent but also have character. In this digital era, children can easily use digital media. The digital era, which not only has positive impacts, but also negative impacts, is a task for educators, parents and adults in guiding and monitoring what children do with their digital media, so that children are able to make the best use of their digital media and get the benefits they need. good for himself and his life Keywords: Character Education; Elementary School; Digital.